Gangguan Fungsi Pendengaran Pekerja Operator di Kawasan Bising Departemen Operasi - Dewi Nata Rina; Tatan Sukwika; Syahfirin Abdullah (The Graduate School of Sahid University, 2021)
Noise in the workplace is a problem for workers, the highest noise intensity measurement in the Operation area is 127.5 dBA which exceeds the Threshold Value. The purpose of this study was to analyze the factors that affect hearing loss. This quantitative research method used a sample of 77 respondents. The analysis used binary logistic regression with cross-sectional to investigate the effect between the dependent and independent variables. The analysis results showed that variables of personal noise dose, work period, hearing protective equipment, history of illness, and hobbies or activities outside of work related to noise significantly affected hearing loss (Sig. ≤ 0,05). In contrast, there was no significant effect between the age variable and hearing loss (Sig. 0.05). It can be concluded that the hearing loss of workers is mostly caused by personal noise dose, work period, use of hearing protection equipment, history of illness, and hobbies or activities outside of work hours related to noise. The managerial implication for the company is to conduct educational socialization that can increase the effectiveness of the use of hearing protection equipment and provide noise management rules as guidance in noise control. Further, enforce regular supervision to ensure noise control implementation, and then implement regular hearing medical check-ups.